2019
DOI: 10.3390/m1099
|View full text |Cite
|
Sign up to set email alerts
|

N-(2-Hydroxy-1,1-dimethylethyl)-3-methylbenzamide

Abstract: The title compound, N-(2-hydroxy-1,1-dimethylethyl)-3-methylbenzamide was synthesized by reacting 3-methylbenzoyl chloride or 3-methylbenzoic acid with 2-amino-2-methyl-1-propanol. In the present report, the synthesized target compound was fully characterized by various spectroscopic methods (1H NMR, 13C NMR, IR, GC-MS), its composition confirmed by elemental analysis, and its structure determined and confirmed by X-ray analysis. The importance of this compound lies in its possession of an N,O-bidentate direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…It is also reported that the latter was essential for the reaction as no reaction was observed without it [19]. In the continuation of our program [20][21][22][23] of the development of directed metal-catalyzed C-H bond functionalization, we wish to report herein the synthesis of a novel amide '4 -methyl-2 -(quinolin-8-ylcarbamoyl)-biphenyl-4-carboxylic acid ethyl ester' by the Ru-catalyzed C(sp 2 )-H bond arylation reaction. The functionalization method employed [RuCl 2 (p-cymene)] 2 as a precatalyst and (p-tol) 3 P as a ligand.…”
Section: Introductionmentioning
confidence: 73%
“…It is also reported that the latter was essential for the reaction as no reaction was observed without it [19]. In the continuation of our program [20][21][22][23] of the development of directed metal-catalyzed C-H bond functionalization, we wish to report herein the synthesis of a novel amide '4 -methyl-2 -(quinolin-8-ylcarbamoyl)-biphenyl-4-carboxylic acid ethyl ester' by the Ru-catalyzed C(sp 2 )-H bond arylation reaction. The functionalization method employed [RuCl 2 (p-cymene)] 2 as a precatalyst and (p-tol) 3 P as a ligand.…”
Section: Introductionmentioning
confidence: 73%
“…The first one involves a weak undirected interaction, due to electrostatic attraction between inhibiting organic ions or dipoles and the electrically charged metal surface. The latter one occurs by sharing or charge transfer from the adsorbate to metal surface atoms, in order to form a coordinated bond; this interaction is known as chemical adsorption or chemisorption [44][45][46]. In order to obtain the adsorption isotherm, the degree of surface coverage (θ) for various inhibitor concentrations was calculated using the equation below, listed in Table 3.…”
Section: Adsorption Isotherm and Adsorption Parametersmentioning
confidence: 99%
“…Such structural requirements have triggered design of novel bidentate directing groups represented by modular triazole-based directing. [9,10] In continuation of our program [11,12] in the design of novel directing groups potentially applicable in metal-catalyzed C-H bond functionalization, we report herein a design-based benzamide bearing 1-aminoanthraquinone (3, Figure 2), a potential N,O-bidentate directing groups for metal-catalyzed C-H bond functionalization. The aminodiketone is commercially available from the Aldrich chemical company at a cheap price rate of 0.092 EUR/mmol (0.412 EUR/g).…”
Section: Introductionmentioning
confidence: 98%